TIMBULAN LEACHATE DARI LANDFILL LYSIMETER DENGAN LAPISAN PENUTUP BERBAHAN DASAR LIMBAH ABU SEKAM PADI - Andy Mizwar (Environmental Research Center (PPLH) of Udayana University, 2015)
The purpose of this study was to determine the effect of the use of rice husk ash as a landfillcover on the quantity and characteristics of leachate generated from landfill lysimeter. Threelysimeters with diameter and height of 0,15 and 2 m, respectively, were prepared. Two lysimeterswere filled with municipal waste and two different cover types i.e. soil (lysimeter A) andricehusk ash (lysimeter B) while another lysimeter was filled solely with municipal waste(lysimeterC). Leachate quantities and characteristics were measured and determined once aweek.The cumulative leachate quantity from the lysimeter B was found to 69,33% and 43,93%lessthan the lysimeter C and Arespectively.Therewereno any differencesof the pH value oftheleachate generated from all lysimeters. The comparison of the leachate characteristicsshowedthat the lysimeter B generate the TSS concentrations 45,95% and 52,93% less thanthelysimeter C and Arespectively,however the TDS concentrations were130,73% and 60,91%morethan lysimeter C and Arespectively.In addition, the use of rice husk ash as a landfillcovercould reduce ± 85% of organic matter in the leachate generated.